Trends and determinants in the utilization of maternal healthcare services in West Bengal, India: Findings from the 3rd and 4th round National Family and Health Survey. (September 2022) - Debsarma, Dhiman; Karmakar, Ranjan; Saha, Jayanti
Abstract: Background: Proper utilization of recommended healthcare services during the pregnancy is considered as critically important for better pregnancy outcomes, as well as a good health status of the mother. Objective: The aim of the current study was to trace the trend in progress, and what are factors associated with the attendance at four Antenatal Care (ANC) visits, receive full ANC and institutional delivery in the study area. Research design/setting: The study has used a cross-sectional secondary data of the 3rd and 4th round National Family and Health Survey (NFHS) for India conducted in 2005-06 and 2015-2016 respectively. For West Bengal, a total of 6794 in 2005-06 and 17, 668 in 2015-2016 ever-married women aged 15-49 who had experienced at least one live birth in the past five years preceding the survey were covered in this study. To analyze the data, the chi-square test was performed as it allows researcher to assess the association between outcome variables and independent variables. The univariate descriptive and multivariate statistical tools have been applied to analyse the data in this study. Results: Our study indicated that the progress rate in attending at least four antenatal care visits, institutional delivery considerably good, but a noticeable gap exists across the different socio-economic groups. The coverage of full ANC services has remained very poor and unchanged over the decade. It was concluded that the wealth status of the households significant predictor of the attendance at least four ANC visits, full ANC and Institutional delivery in West Bengal. Other statistically significant socio-economic and demographic factors include level of women education, age of women, exposure to mass media, place of residence, and number of parities of birth. Conclusion: The present study suggests that the increasing strength in the coverage of all maternal healthcare services could be a significant focus during the program implementation in West Bengal. For strengthening and ascertaining the universal coverage of maternal healthcare services, there is an urgent need to reduce socioeconomic inequity in uses of the recommended maternal healthcare services. Moreover, our study found that the socio-economic and demographic factors play a significant role in utilization of maternal healthcare services. Thus the promotion of women education, empowerment and autonomy, and the frequent social marketing of government schemes and programs on maternal healthcare through the various types of mass media should be the unique future steps for achieving the universal coverage of maternal service in West Bengal.